2011
DOI: 10.1159/000323263
|View full text |Cite
|
Sign up to set email alerts
|

Primary Primitive Neuroectodermal Tumor of the Conus Medullaris in an Elderly Patient: A Case Report and Review of the Literature

Abstract: Primary spinal primitive neuroectodermal tumors (PNETs) are very rare conditions. Most of these tumors occur in children and young adults. A 63-year-old man with a primary spinal PNET in the conus medullaris from the L1 to L2 level is presented in this report. The optimal treatment of primary spinal PNETs is yet unknown. Surgical resection, radiation therapy, and chemotherapy have been advocated for the treatment of spinal PNET based on PNETs at other sites. However, the outcome is very poor. There are a few r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…5 Previous studies have shown that CD99 has a high sensitivity and specificity for primary spinal pPNETs, which might obviate the need for chromosomal studies, though chromosomal studies can be complementary to achieving a definite diagnosis. 5,21 Besides, NSE, Syn, S-100, vimentin, and CD56 are commonly expressed in pPNETs, while pNETs often have negative staining for GFAP, which is also useful for reaching a differential diagnosis. 22 Due to the rarity of the disease, there are no standard therapeutic strategies to treat primary spinal PNETs.…”
Section: Discussionmentioning
confidence: 99%
“…5 Previous studies have shown that CD99 has a high sensitivity and specificity for primary spinal pPNETs, which might obviate the need for chromosomal studies, though chromosomal studies can be complementary to achieving a definite diagnosis. 5,21 Besides, NSE, Syn, S-100, vimentin, and CD56 are commonly expressed in pPNETs, while pNETs often have negative staining for GFAP, which is also useful for reaching a differential diagnosis. 22 Due to the rarity of the disease, there are no standard therapeutic strategies to treat primary spinal PNETs.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of spinal PNETs are the result of the subarachnoidal spread of tumors in the neuraxis. 8 Before the diagnosis of primary spinal PNET can be confirmed, the more common "drop" metastases of intracranial origin must be excluded. 9 This is the main reason why the patient underwent cranial and whole spine MRI before starting craniospinal irradiation (CSI) and concurrent chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor usually presents with nonspecific symptoms such as paraparesis, paresthesias, gait disturbance, and low back pain as in our case. [ 10 11 ] MRI features of PNET are also usually nonspecific, with most of them being hyperintense on T2-WI and iso- to hypointense on T1-WI, with heterogeneous enhancement on postcontrast sequences. In our case, it was hypointense on T1-WI and T2-WI and had no obvious contrast enhancement.…”
Section: Discussionmentioning
confidence: 99%